Characterisation of Recombinant Aryl Hydrocarbon Receptor Ligand Binding Domain - Jiang, Tao (2004)
Aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor, which mediates the toxicity of dioxin and related compounds, and has an important role in development. However, a structural basis for ligand binding to the AhR remains unclear and the study was hindered by the low abundance and inherited instability of the AhR. Based on a previously defined minimal ligand-binding domain (LBD, residues 230-421), in the present study a series of truncated LBD constructs were created and expressed in insect cells (Sf9) using a baculovirus expression system. An antibody was produced to analyze the expressed. The antisera can detect as low as 0.3ng of AhR LBD from cytosol of Sf9. An in vitro [3H]TCDD binding assay was developed to characterized the expressed LBD. The assay yielded an estimate for the KD of C57Bl/6 mouse liver binding at 1.4nM. The present expression system yields soluble AhR LBD protein at ~0.15% of cytosol protein. Supplementation of the Sf9 culture medium with additional glucose resulted in an increase in the amount of soluble AhR, due to an increase in intracellular ATP level. However, cotransfection of LBD with hsp90 interaction protein p23 made no substantial change in the amount of cytosolic AhR. The soluble recombinant LBD retains functionality in the form of specific binding to dioxin, and its thermal stability was indistinguishable from that of mouse liver. However the ligand-binding activity of LBD was molybdate dependent, indicating a weaker association of mouse AhR LBD with Sf9 hsp90. A differential effect of Triton X-100 on the recombinant AhR LBD and native AhR also suggests that the interaction between AhR and Sf9 hsp90 is less stable. The study refined the minimal LBD to a region of 125 amino acids, which should be amenable for structural studies of the LBD.